New Residential Districts Ordering: from Language of Smells Description to the Space Sensory Order - Ekaterina Sergeevna Shishova (Интеракция. Интервью. Интерпретация, 2020)
The article analyzes the sensory aspects of urban life in one of the districts in the outskirts of Moscow. Revising the concepts of sensory ordering of space, I analyze the ways how urban dwellers in this district order the space by smell perception. I define three components of sensory ordering: i) the language of sensory experience, ii) ascription of meanings to space and smells localization, iii) actions aimed at supporting the desirable olfactory landscape. The process of creating this language and negotiations about the desirable olfactory landscape are based on adopting the special terms and visualizing the smells. This language allows to interact with the various agents on different levels of power, to transform and control the space. The production of meanings, based on smells, influences the district identity. Both positive and negative smell perception produce the value of the district, while the negative smells acts differently and devalues the other city territories. Citizens actions support the sensory normativity: through sensory patrolling (different ways of detecting the smells) and microordering (creating the cleanliness and freshness within neighborhoods). These ways of ordering sensory experience and creating olfactory landscape help to explain the interaction between district dwellers, the principles of how their agency is formed, and the principles of being responsible for the space.